2020
DOI: 10.1093/jaoacint/qsaa015
|View full text |Cite
|
Sign up to set email alerts
|

Review of New Trends in the Analysis of Allergenic Residues in Foods and Cosmetic Products

Abstract: Background Allergies represent an important health problem in industrialized countries. Allergen sensitization is an important risk factor for the development of allergic diseases; thus, the identification of an individual’s allergen sensitization is essential for the diagnosis and treatment of diseases. Objective This review compares different modern methods applied for the analysis of allergens in various matrices (from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Several physicochemical methods like fluorescence spectroscopy, far-UV circular dichroism, Fourier-transform infrared spectroscopy (FTIR) and online-high performance size exclusion chromatography (HPSEC) light scattering have been shown to provide insight into questions not addressed by immunoassays, like information on protein structures or molecular weight distributions in allergen extracts ( 77 – 79 ). In comparison, mass spectrometry (MS) has the potential to replace standard immunoassays due to its high accuracy not only for detection but also for quantification of allergenic proteins in complex samples ( 80 , 81 ). MS systems are normally defined according to the different types of their three basic components, i.e .…”
Section: Potential Of Alternative Methods In Allergen Product Standardizationmentioning
confidence: 99%
“…Several physicochemical methods like fluorescence spectroscopy, far-UV circular dichroism, Fourier-transform infrared spectroscopy (FTIR) and online-high performance size exclusion chromatography (HPSEC) light scattering have been shown to provide insight into questions not addressed by immunoassays, like information on protein structures or molecular weight distributions in allergen extracts ( 77 – 79 ). In comparison, mass spectrometry (MS) has the potential to replace standard immunoassays due to its high accuracy not only for detection but also for quantification of allergenic proteins in complex samples ( 80 , 81 ). MS systems are normally defined according to the different types of their three basic components, i.e .…”
Section: Potential Of Alternative Methods In Allergen Product Standardizationmentioning
confidence: 99%
“…Recently, Ito et al proposed sodium sulfite as a potential eco-friendly reductant alternative to 2-ME [ 61 ]. Application of the modified extraction buffer on different matrices (egg, milk, wheat, peanut, and buckwheat) showed that the protein extraction efficiency of SDS/0.1 mol L −1 sodium sulfite solution was comparable to that of SDS/2-ME [ 62 ]. Dedicated analytical devices for the detection of food allergens have also been developed.…”
Section: Food Matrices and Sample Pretreatment For Portable Biosensorsmentioning
confidence: 99%
“…The analysis of cosmetics represents a challenge mainly because of the great variety of ingredients and formulations leading to immense matrix complexity and variability. In this field, many analytical techniques play a crucial role, each designed to meet specific demands to understand the molecular nature of cosmetic products and the complexity of their formulations: chromatography (liquid chromatography (LC) [ 5 , 6 ], gas chromatography (GC) [ 7 , 8 ], supercritical fluid chromatography (SFC) [ 9 ], capillary electrophoresis (CE) [ 10 , 11 ], spectroscopy [ 12 , 13 , 14 , 15 , 16 , 17 ], electrochemistry [ 18 ], colorimetry [ 19 , 20 ], mass spectrometry (MS) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], interfacial methods [ 32 , 33 ], rheological assessment [ 34 , 35 , 36 ], olfactometry, and electronic nose technology [ 37 , 38 , 39 ]. Recent advances in MS and ionization techniques provide access to richer and deeper information on monitoring the molecular compositions of endogenous or exogenous compounds in or on the skin as well as those used in cosmetic formulations, with less time and effort.…”
Section: Introductionmentioning
confidence: 99%